An extraction method of positive blood cultures for direct identification of Candida species by Vitek MS matrix-assisted laser desorption ionization time of flight mass spectrometry. (August 2013) - Lavergne, Rose-Anne; Chauvin, Pamela; Valentin, Alexis; Fillaux, Judith; Roques-Malecaze, Christine; Arnaud, Sylvie; Menard, Sandie; Magnaval, Jean-François; Berry, Antoine; Cassaing, Sophie; Iriart, Xavier
Abstract Candida spp. are an important cause of nosocomial bloodstream infections. Currently, complete identification of yeasts with conventional methods takes several days. We report here the first evaluation of an extraction method associated with the Vitek MS matrix-assisted laser desorption ionization time of flight mass spectrometry for direct identification of Candida species from positive blood cultures. We evaluated this protocol with blood cultures that were inoculated with reference and routine isolates (eight reference strains, 30 patients isolates and six mixed cultures containing two strains of different Candida species), or from patients with candidemia (28 isolates). This method performed extremely well (97% correct identification) with blood cultures of single Candida spp. and significantly reduced the time of diagnosis. Nevertheless, subculture remains indispensable to test fungal resistance and to detect mixed infections.